Tax exemptions to public benefit organisations: reform in respect of South African churches - Banda, Nico Valand (My University, 2021)
The right to religion and to form religious organisations and associations is enshrined in the Constitution of South Africa, 1996. Religious organisations play an important role in the furtherance of these rights and have been accepted as public benefit organisations in terms of the Income Tax Act 58 of 1962 and can apply for tax benefits that have been afforded to public benefit organisations. However, South Africa has in the past few years seen an increase in news articles regarding the commercialisation of religion as well as profit driven churches being used as wealth creation tools for church leaders. The Commission for the Promotion and Protection of the Rights of Cultural, Religious and Linguistic Communities (The CRL Commission) undertook an investigation into the issue of commercialisation of religion and found the issue of commercialisation to be true. The CRL Commission found various issues including the intentional disregard of accounting, financial and tax rules. The Commission found that various organisations were never registered, submitted no tax returns, and kept no financial records with some organisations intentionally doing so to evade taxes. The CRL Commission attributed the commercialisation of religion to a lack of enforcement as well as gaps in the legislation such as the lack of mandatory registration of these organisations. This paper examines how the current tax regime that affords exemptions to public benefit organisations can be developed to address the issue of commercialisation of the church. The paper shows that religious organisations do play a public benefit role in South Africa, they have the ability to provide social services to communities in South Africa that the government struggle to reach such as the provision of housing. However, there is a need to address the use of religious organisations by religious leaders who look to enrich themselves. The paper proposes making registration mandatory but goes further to recommend that religious organisations no longer be governed under the Income Tax Act 58 of 1962 but that a separate legislation adopting the approach taken with the Estate Duty Act 45 of 1955 be legislated as a guiding legislation to regulate the administration and taxation of religious organisations
A research report submitted in partial fulfilment of the requirements for the degree of Master of Laws (by Coursework and Research Report) at the University of the Witwatersrand, 2021